2015
DOI: 10.1007/s00384-015-2262-2
|View full text |Cite
|
Sign up to set email alerts
|

Management of rectourinary fistula after urological interventions using biodesigned mesh: first experiences of an innovative technique

Abstract: Management of rectourinary fistula is still challenging. Using biomaterials for fistula closure seems to be a promising and minimally invasive transanal technique in future. Further analysis including more patients is needed to clarify its exact role in comparison to traditional surgical techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Some authors have recently reported their experience treating the RUF trans-anally with the use of biological mesh covered by a tension free-well vascularised rectal wall flap [11][12][13]. Acellular dermal matrix (biological mesh) is potentially advantages to reduce risks of infection or rejection.…”
mentioning
confidence: 99%
“…Some authors have recently reported their experience treating the RUF trans-anally with the use of biological mesh covered by a tension free-well vascularised rectal wall flap [11][12][13]. Acellular dermal matrix (biological mesh) is potentially advantages to reduce risks of infection or rejection.…”
mentioning
confidence: 99%